Pembangunan Arsitektur WebGIS Untuk Pemetaan Daerah Yang Terdampak Erupsi Gunung Merapi (Studi Kasus: Kabupaten Sleman) - Ahmad Arif Saputra; Fatwa Ramdani; Suprapto Suprapto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Sleman District is one of the largest areas affected by the eruption of Merapi Mountain. According to interviews with Badan Penanggulangan Bencana Daerah (BPBD) of Sleman Regency, Merapi Mountain is predicted to erupt anytime in the near future. Some conditions that support it among others the activity of lava is still high, the lava is increasingly reaching the surface, the lava pipe used as a lava exit and hot steam has been enclosed by hardened lava. Currently, BPBD does not yet have any data related to areas affected by eruption in each year in the form of maps. This data can be used as data for disaster mitigation and predict the large of areas that may be affected in the event of another eruption. To obtain the data, supervised classification technique will be used by using Semi Automatic Classification Plug-In (SCP) from Quantum GIS application. This technique is used for mapping erupted areas in Sleman District by defining polygon training data. Then the results of the mapping will be displayed by using Web-based Geographic Information System (WebGIS), so it can provide the mapped results properly and clearly for users. WebGIS architecture is divided into 3 layers, i.e. Client Layer, Service Layer, and Support Layer. Based on the mapped results, it was found that the eruption of 2010 was an eruption that had the greatest impact with the area of 3.309,55 ha and the percentage of 47.6%. While the accuracy test results obtained the accuracy is 92% and the precision is 86.2%, which means that the mapping results have high accuracy and precision.